Pengamatan Sistem Informasi Perusahaan E-Commerce Lazada Indonesia - Sayyidah Amalia Rokhimah; I Kadek Adi Gilang Pratama; Kenneth Daniel; I Made Dwi Sugiarta Putra; Diani Arviana Jaya; Muhammad Vito Arya Apriza; Tiawan (Primakara University, 2022)
Rapid technological developments have a significant impact on various sectors of life, as well as in the digital business development sector. The dependence of society on technology has now penetrated into all factors of social and social life. Utilization and use of technology is now increasingly widespread, one of which is the use of information systems in conducting various transactions on online media that can be accessed on e-commerce pages. Kominfo noted that Indonesia is in the 6th position as the country with the most internet users in the world. In 2018, the number of internet users in Indonesia reached 202.6 million. This figure proves that Indonesia has a wide market opportunity, this can also be seen from the many foreign e-commerce companies that have started to target Indonesia as the target market. Among the many e-commerce platforms in Indonesia, Lazada is one that is quite popular and is currently widely used by the people of Indonesia. Lazada Indonesia was founded in 2012 and is one of the branches of the Lazada online retail network in Southeast Asia. Lazada Southeast Asia is a subsidiary of the Rocket Internet network, a German company. Lazada Indonesia's popularity as an e-commerce platform makes it a marketplace with 28 million visitors per month. However, it takes an in-depth observation and analysis on e-commerce sites to determine an effective strategy to design a compatible information system. The results of the observations that we analyze on the e-commerce company, namely Lazada Indonesia, which has many users who use Lazada as a place to buy and sell. Our observations are also from the FlowChart that we made aims to make it easier for us to present how or how to use Lazada. The benefit of the Use Case is used as a verification requirement and becomes an interface description of a system because every system that you want to build must also have an interface and be able to identify anyone who can interact with the Lazada Indonesia system and provide certainty about system requirements so that it is not confusing.